Analysis of the Advisory Opinion of the International Court of Justice for Western Sahara Issued on October 16th, 1975 - Zenati, Mustapha (Journal of Legal Studies and Researches, 2022)
The advisory opinion of The International Court of Justice for Western Sahara Issued on October 16, 1975 is a major significant victory of the Sahrawi people under the Moroccan colonial. The desert issue is the only one in Africa, which has been stuck since 1975 without the procedure of self-determination due to Morocco.